The exhibition of the other: tradition, memory and colonialism in museums in Mexico - Mario Ruffer (Antíteses, 2014)
This article starts from the notion of "complex exhibitorio" on classical pedagogical function of the Western Museum (historical and ethnographic), and reviewed in, specifically Mexican contemporary Latin American contexts. The text contrasts ethnographic work in community museums with certain aspects of the Boards of ethnography at the National Museum of Anthropology in Mexico. The central thesis seeks to demonstrate is that the current rhetoric of post-colonial heritage and "cultural diversity" environments, still using the logic of exhibitorio complex but with a different mechanism and the classical notion of early twentieth century end. No longer try to exhibit the feats of the modern order and national construction, but a poetic return. Tradition would no longer fixed forever in the national museum in the capital, but that is installed on the spatial distance of the town or village: those who were the subject of museum and exhibition become subject to production of a look and an order. Finally he asks: have really moved the mechanisms defined and retained authority over cultural heritage?